Tracking control a twin-rotor helicopter used for building measuring with PID-MPC controller. Issue 1 (1st April 2022) - Guo, F
Abstract: In recent years, due to the development of UAV (Unmanned aerial vehicle) technology, UAVs have been used in an increasingly wide range of applications, including the architecture industry. In the field of architecture, the technologies of capturing images of building conditions with UAVs have a huge development, such as architectural planning, remote terrain detection, construction safety supervision and so forth. In general, the applications can be expanded widly, owing to the convenient operation of UAVs for the flyers and that does not require a high degree of precision for the control. However, when it comes to penetration between and within buildings. The lack of flight vision and signal interference often leads to collisions and crashes. Hence, this paper studies how to further optimise the control accuracy of construction measurement UAVs. The aim is to reduce the difficulty of operating the UAV when it faces to interference during architecture measurement. In this paper, a three DOFs two-rotor UAV is selected as the object of study. A mathematical model of the UAV is constructed, which is followed by the designing of an advanced controller based on a PID controller and an MPC (model predictive controller) controller, used for realising offset free reference tracking when changing elevation, pitch and travel angles. The usage of this controller can significantly reduce the cost of control during flight to reduce control bias in the presence of disturbing factors. The application of the controller to UAVs allows for automated and intelligent UAV control.